MODEL PENDIDIKAN ISLAM SUKU ANAK DALAM DI JAMBI (Studi Etnografi Di Taman Nasional Bukit 12 Air Hitam Sarolangun) - Ema Lestari; Saeful Anam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This thesis abstract discusses the Islamic education model of the Anak Dalam Tribe in Jambi, specifically in Bukit 12 Air Hitam Sarolangun National Park. This study aims to investigate the practice of Islamic education in this community, focusing on the educational conditions for Anak Dalam children, suitable Islamic education models, as well as the inhibiting and supporting factors in its implementation. The study employs a qualitative approach using ethnographic methods. Data were collected through participant observation, in-depth interviews with traditional leaders, religious leaders, community members, and relevant parties, as well as documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. This research is expected to provide theoretical contributions to the advancement of scholarly studies in Islamic education, particularly regarding the development of a contextual and adaptive Islamic education model for indigenous communities. In addition, the results of this study are expected to serve as a practical reference for Islamic educational institutions, the government, and social organizations in designing Islamic education models suitable for the Anak Dalam Tribe in Jambi. This study also aims to identify local cultural values that can be integrated into Islamic education, thereby contributing to the development of the character and morals of the younger generation.